European Quality Labels - a Visual Source of Consumer Information on Traditional Products An Empirical Study from Poland on Labels Recognition and Information Seeking Behavior - Inga OLEKSIUK (Communications of International Proceedings, 2021)
There are many instruments that help consumers in the decision-making process regarding the purchase of food. As far as traditional products (TP) are concerned, European quality labels (EQL) play an important informative function. (EU Regulation 1151/2012). The author provides a normative and applicative evaluation of European quality symbols as a source of consumer information. The research combines a critical analysis of primary and secondary materials with quantitative empirical research. The author analyzed data collected from 632 Polish respondents with the use of the diagnostic survey method (2018-2021). In this scope, the level of recognition of EQL was determined and communication channels about traditional products were indicated. Based on these findings, the author discusses how to increase the visibility of EQL. In Poland, the awareness of EQL was considered modest, with the exception of the Traditional speciality guaranteed,  which was moderate. The findings indicate that communication relating to TP should be based on the personalization of the message, authenticated by direct communication. Both physical and online contact are relevant. Another important conclusion refers to the links between agricultural policy and the development of local communities. In this regard the author supports the recommendation of the EU AGRI Report (2020) and claim that synergies between EQL and tourism should be further developed, including the application of quality labels to traditional non-food products.
Keywords: Consumer Information; European Quality Labels. Traditional Products